A Comprehensive Review on Long-term Care Policies for Intellectual and Developmental Disabilities - Puja Suri; Sangeeta Kakkar; Ritika Chauhan (International Journal of Trends in Humanities, 2024)
Intellectual disability (ID) is a neurodevelopmental difficulty that affects both intellectual functioning and adaptive behaviour. The term IDD describes a broad range of long-term disorders that are caused by either physical or mental deficits. These disorders can influence numerous facets of life, such as self-care, social skills, communication, and education. This condition affects social and practical abilities daily. Conditions like cerebral palsy, Down syndrome, and autism spectrum disorder, Genetic predispositions, prenatal problems, traumatic births, and diseases in the early years can all lead to IDD. The foremost aim of this review is to provide awareness of Long-Term care policies that are available for IDD people. The review discovered the main obstacles and difficulties that people with IDD have while trying to get access to high-quality long-term care. It also examined the efficacy of current long-term care programs, compared strategies, and identified promising innovative models. The evaluation looked at past patterns, evaluated the success of ongoing initiatives, and pinpointed areas that need improvement. It also looked at current developments in care paradigms and technology. The review indicated that although LTC policies have improved, there are still issues and shortcomings that need to be addressed. It is stressed how crucial long-term planning and caregiver assistance are. People with IDD and their families may suffer as a result of inadequate LTC plans. The review emphasized how better policy is required.
Keywords: Intellectual developmental disabilities (IDD); Long Term Care (LTC); caregiver assistance; innovative care models; neurodevelopmental difficulty